Nutritional properties of underutilized legumes and intercropped maize - Ayilara, Modupe S.; Abberton, Michael; Oyatomi, Olaniyi A.; Odeyemi, Olu; Babalola, Olubukola O. (Frontiers in Soil Science, 2023)
This study was conducted to evaluate the effect of intercropping on the nutritional (ash, moisture, fat, protein, carbohydrate, tryptophan) and anti-nutritional (phytate and tannin) qualities of five accessions of African yam bean (AYB) and five accessions of winged bean (WB) when separately intercropped with two accessions of maize. The research was carried out at the Food and Nutrition Sciences Laboratory, International Institute of Tropical Agriculture Ibadan, Nigeria. In the legumes, intercropping with M2 led to a reduction in the moisture content of AYB accessions TSs4, TSs30, and TSs77, an increase in the moisture content in WB accession Tpt51 when intercropped with both maize accessions, a reduction in the protein content of AYB accessions TSs4 and 101 when intercropped with both maize accessions, an increase in the protein content of AYB accession TSs30 and WB accession 15-4 when intercropped with M2 and an increase in the protein content of WB accession Tpt51 intercropped with M1. Similarly, intercropping increased the phytate contents in AYB accession TSs4, and WB accessions Tpt12, 15-4 and Tpt32 intercropped with the two maize accession, it also increased the phytate content when M2 was intercropped with TSs30 and Tpt51, it reduced the tannin content in WB accession Tpt12 intercropped with both maize accessions, and increased the tannin content in AYB accessions TSs4, TSs101, and WB accessions 15-4, and Tpt32 when intercropped with both maize accessions. For the maize grains, intercropping with AYB led to a reduced tannin content in both maize accessions. Intercropping increased the moisture content of M1 when intercropped with AYB accessions TSs101 and TSs68, while that of M2 reduced when intercropped with AYB accessions TSs101, TSs4, TSs68 and TSs30. In addition, intercropping reduced the protein content in M1 when intercropped with Tpt12, Tpt32, and Tpt51. Finally, intercropping increased the fat content in both maize accession, increased the tryptophan content of M1 when intercropped with Tpt32, and increased the carbohydrate content in M1 intercropped with Tpt51.